2015
DOI: 10.1111/jen.12221
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of slow and fast development in predatory ladybirds

Abstract: The frequency distribution of the durations of development of 516 larvae of Adalia bipunctata is unimodal, and the fast-and slow-developing larvae can be identified at the beginning of the fourth (=last) instar. To determine the advantages of fast and slow development, the survival, duration of development, growth and number of aphids consumed by fast-and slow-developing fourth instar larvae fed different numbers aphids were recorded. The percentages of fast-and slow-developing fourth instar larvae that surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…This may also act as a counterbalancing force that preserves the slow developing individuals in the population. Dixon et al (2015) reported that the optimum growth rate of a predator is positively associated with that of its prey and that plays a crucial role in evolution. The variation in responses with change in prey is similar to that witnessed in these two ladybirds at varying temperatures under ad libitum prey supply (Singh et al, 2014(Singh et al, , 2016.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may also act as a counterbalancing force that preserves the slow developing individuals in the population. Dixon et al (2015) reported that the optimum growth rate of a predator is positively associated with that of its prey and that plays a crucial role in evolution. The variation in responses with change in prey is similar to that witnessed in these two ladybirds at varying temperatures under ad libitum prey supply (Singh et al, 2014(Singh et al, , 2016.…”
Section: Discussionmentioning
confidence: 99%
“…Such an inherent variation in developmental rate has also been reported in salmonid fish (Gross, 1985), butterflies, Maculinea rebeli (Hirchke) (Schönrogge et al , 2000; Witek et al , 2006) and Bicyclus anynana (Butler) (Lewis et al , 2010), predaceous syrphid, Microdon mutabilis (L.) (Schönrogge et al , 2000), nematode, Teladorsagia circumcincta (Stadelman) (Skorping, 2007) and other insects (Gouws et al ., 2011) including ladybirds (Mishra & Omkar, 2012; Singh et al , 2014, 2016; Dixon et al , 2015). Though, not commonly assessed, but in ladybirds this inherent variation in developmental rates within the same cohort and population has been observed (Rodriguez-Saona & Miller, 1995; Dixon, 2000; Mishra & Omkar, 2012; Singh et al , 2014, 2016; Dixon et al , 2015), albeit their distribution pattern has not been assessed until recently (Mishra & Omkar, 2012; Singh et al , 2014, 2016; Dixon et al , 2015). The lack of unanimity about bimodality of developmental durations of ladybirds could simply be a result of very few studies on their growth and development attempting to assess the distribution of development rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Siddiqui et al (2015) report that mutual interference of slow and fast developing ladybird, Propylea dissecta (Mulsant) were −0.394 and −0.808, respectively, indicating that fast developers search more efficiently and spend less time interacting with conspecifics. Fast developers tend to eat faster than slow developers and are heavier and lay more eggs than the latter (Singh et al 2014;Dixon et al 2016). Mutual interference values for unparasitized and parasitized larvae of Nephus includens (Kirsch) were −0.44 and −0.92 respectively, indicating that interference reduces the foraging capacity of parasitized more than that of unparasitized larvae (Bayoumy and Michaud 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, for predators, the optimal strategy involves counteracting pressures to maximize their own reproduction and survival while conserving enough prey to sustain a sufficient food supply for their offspring. This is very nicely exemplified by long-lived insect predators, such as ladybirds, feeding on short-lived prey, such as aphids (Dixon and Kindlmann 1998;Kindlmann and Dixon 1999a, 1999b, 2001Dostálková et al 2002;Dixon et al 2015). As most of these predators suffer enormous egg and larval mortality due to cannibalism (Dixon and Kindlmann 2012) and intraguild predation (Mills 1982), selection acts mainly on optimizing their oviposition strategies in terms of maximizing the likelihood that their offspring will survive until reproductive age.…”
Section: Optimal Strategy Of An Aphid Predatormentioning
confidence: 99%